Association of oropharyngeal cancer HPV status with diffusion-weighted MR imaging and FDG-PET parameters - Fabian Kalt; Martin Hüllner; Moritz C. Wurnig; Gregoire B. Morand; Martina A. Broglie; Paul Stolzmann; Martin Lanzer (Advances in Oral and Maxillofacial Surgery, 2024)
Background: Human papilloma virus (HPV) infection is an important risk factor in oropharyngeal cancer. Several studies have analyzed the association of tumoral HPV status and different imaging parameters in FDG-PET/CT and magnetic resonance (MR) diffusion-weighted imaging (DWI), with contradictory findings. In this retrospective study, the influence of HPV-status on different parameters in FDG-imaging and MR DWI is investigated. Methods: In this retrospective, single-center study we analyzed patients diagnosed with oropharyngeal cancer between January 2018 and December 2020 at a tertiary center in Switzerland. HPV status was assessed via p16 immunohistochemistry and/or PCR. Standardized uptake value (SUV), total lesion glycolysis (TLG) and apparent diffusion coefficient (ADC) were measured in pretreatment imaging (FDG-PET/CT, FDG-PET/MR, DWI MR). Statistical analysis was performed using Mann-Whitney-U tests. All p values reported are two-sided, and p values < 0.05 were considered statistically significant. Results: 142 patients were included. 67% of tumors were HPV-positive. Mean SUVmax in FDG-PET was 15.0+/-5.9 for HPV-positive tumors and 18.6+/-9.7 for HPV-negative tumors (p = 0.15). Mean ADC was 1109 x 106 mm2/s+/-326.8 for HPV-positive tumors and 1045.8 x 106 mm2/s+/-467.0 for HPV-negative tumors (p = 0.76). Conclusion: and Relevance: We found no correlation between oropharyngeal carcinoma HPV status and any of the analyzed imaging parameters.